Urgency of Noble Characters’ Education and Building Students’ Prosocial Behaviors - Safrilsyah, Safrilsyah; Ibrahim, Ibrahim; Marwan, Marwan; Yusoff, Mohd. Zailani Mohd.; Subhan, Subhan; Darusman, Mhd. Ricky (SCAD Independent, 2024)
The rapid advancement of information technology challenges Muslim youths, fostering individualism and antisocial behaviors, thus necessitating effective education strategies to promote prosocial actions. This research aimed to summarize studies on the formation of prosocial behavior through character education methods from the synthesis of several studies and review effective methods for developing prosocial behavior. This research used a literature review method for several articles about social behavior and character education. Data collection was carried out by studying the documentation of several previous articles through database searches such as Google Scholar, Sinta, Science Direct, and Taylor and Francis. The data analysis technique used was qualitative descriptive analysis. The results of this research indicated that the noble character development method will be effective in forming prosocial behavior. The character education method by focusing on the appreciation of noble moral values in character education produced positive habits. The process of realizing noble moral values was through various moral education methods, such as Tadzkiroh, the religious lessons with regular Islamic discussion activities that combined subjects with noble moral values and exemplary methods.